A Comprehensive Review on Phytochemical, Pharmacological, Dielectric and Therapeutic Attributes of Multifarious Rudraksha (Elaeocarpus Ganitrus Roxb.) - Maheshwari, Raaz K.; Kumar , Anil; Punar, Sukhraj; Ram, Lakha; Sharma, Ravi; Kakodia, Ashok K.; Rani, Bina; Singh, Upma (European Journal of Applied Sciences, 2021)
In traditional system of medicine, different parts (beads, bark, leaves and outer shell of beads) of Rudraksha are considered for the alleviation of various health problems such as mental disorders, headache, fever, skin diseases and for healing the wounds. Ayurvedic texts categorize Rudraksha fruits as thermogenic, sedative, cough alleviator and are useful for the treatment of bronchitis, neuralgia, cephalagia, anorexia, migraine, manic conditions and other brain disorders. It is employed in folk medicine as a counter agent of stress, anxiety, depression, palpitation, nerve pain, epilepsy, lack of concentration, asthma, hypertension, arthritis and liver diseases. Furthermore it is retrieve to exhibit diversed pharmacological activities like anti-inflammatory, analgesic, hypoglycemic, antiulcerogenic and very high antimicrobial activity. phytosterols, alkaloids, flavonoids, carbohydrates, proteins, fats and tannins have been found to be largely responsible for the therapeutic potential of E.ganitrus. Significant amount of phytocomponents such as isoelaeocarpicine, elaeocapine isoelaeocarpine and quercetin, gallic, ellagic acids and rudrakine have been found to occur in rudraksha.In the present review, an attempt has been made to congregate the botanical, phytochemical, ethno medicinal, pharmacological information on Elaeocarpus ganitrus Roxb.